PENGARUH KOMPENSASI, LINGKUNGAN KERJA, KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KEPUASAN KERJA KARYAWAN PT PG RAJAWALI 1 UNIT PG KREBET BARU MALANG - Afifah Ardiyanti Pramesti; Abdul Kodir Djaelani; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT:This  study  aims  to  determine  the  effect  of  competation,  work  environment,  occupational  safety  and  healt  (K3)  on  employee  satisfaction  in  the  HR  department.  The  research  sample  consisted  of  61  HR  employees  at  PT  PG  Rajawali  1  Unit  of  the  New  Malang  Krebet  using  the  stratified  proportional  random  sampling  method.  Is  a  quantitative  research  that  uses  questionnaires  and  documentation  data  collection.  Using  multiple  linier  regression  analisys  with  the  help  of  the  application  SPSS  14.0  for  windows.            The  result  prove  if  the  compensation  variable,  work  environment,  and  occupational  health  variable  do  not  have  positive  effect  on  job  satisfaction  while  the  safety  variable  had  a  positive  effect  on  job  satisfaction  on  PT  PG  Rajawali  employees  1  Unit  of  the  new  poor  Krebet  Malang.Keywords:  Compentation,  Work  Environment,  Occupational  Safety  and  Health  (K3),  Job  Satisfaction.